1988
DOI: 10.1063/1.455394
|View full text |Cite
|
Sign up to set email alerts
|

Postattachment interactions in K(n d)–SF6 collisions at intermediate n

Abstract: Rate constants for Rydberg atom destruction and for free SF−6 ion formation in K(nd)–SF6 collisions at intermediate values of n are reported. The data show that the rate constants for collisional destruction are consistent with those expected on the basis of Rydberg electron attachment to SF6, but that only a fraction of such events lead to an observable SF−6 ion. This fraction can, however, be significantly increased by application of an external electric field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…O -; this ion has also been observed as the dominant species by K n a p p et al [8] and K o n d o w [5] in attachment reactions of N 2 0 clusters with free electrons at energies below 10 eV and by K o n d o w [5] in collisions with unselected Kr** Rydberg atoms (estimated range of contributing principal quantum numbers 25-35). The rate constant k,e (SF6-) for SF6 formation has been studied before [21] and is well characterized [14][15][16][17][18][19][20][21]; for vat = 560 m/s, k,d(SF6) is essentially constant for n > 24 and progressively decreases towards lower n (at n = 10, it is down by about a factor of 10). At high n, a rather narrow distribution of (N20)q-Oand (N20)q ions is found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…O -; this ion has also been observed as the dominant species by K n a p p et al [8] and K o n d o w [5] in attachment reactions of N 2 0 clusters with free electrons at energies below 10 eV and by K o n d o w [5] in collisions with unselected Kr** Rydberg atoms (estimated range of contributing principal quantum numbers 25-35). The rate constant k,e (SF6-) for SF6 formation has been studied before [21] and is well characterized [14][15][16][17][18][19][20][21]; for vat = 560 m/s, k,d(SF6) is essentially constant for n > 24 and progressively decreases towards lower n (at n = 10, it is down by about a factor of 10). At high n, a rather narrow distribution of (N20)q-Oand (N20)q ions is found.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the attachment of free electrons [6][7][8][9][10] an interesting alternative has been recently developed by Kondow and colleagues [5], who investigated the mass spectra of negative cluster ions, formed in single collisions of skimmed nozzle beams with electron beam excited rare gas Rydberg atoms Rg**. The principle quantum number n of the Rg** atoms was estimated to be in the range 25-35. An obvious and interesting extension of their method is the use of state-selected Rydberg atoms A**(n/) at low, intermediate, and high n. Such studies are suited -as shown for electron transfer to elementary molecules [14][15][16][17][18][19][20] -to obtain detailed information on the reaction mechanism and its dependence on electron (binding) energy. The principle quantum number n of the Rg** atoms was estimated to be in the range 25-35. An obvious and interesting extension of their method is the use of state-selected Rydberg atoms A**(n/) at low, intermediate, and high n. Such studies are suited -as shown for electron transfer to elementary molecules [14][15][16][17][18][19][20] -to obtain detailed information on the reaction mechanism and its dependence on electron (binding) energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides our own work [12,14] (12 < n-< 40), and by Walter et al [26] on K(nd)+O2 (8<n_<12). Very recently, Carman et al [27] investigated electron transfer in the systems CS (n s, n d) + S F 6, CC14 ( 12 --< n N 40), Zheng et al [28] studied Rydberg atom destruction and SF6 ion formation in the system K(nd)+SF6(12<_n<20), and Kalamarides et al [29] looked at negative ion formation in K (n d) + CS2 collisions (10 _< n _< 20).…”
Section: Introductionmentioning
confidence: 98%
“…The core certainly plays a role in these collisions-at least for atoms excited to low lying excited states. The strong Coulombic attraction between the nascent positive and negative ions (especially at lower n) acts to prevent the ions from separating, resulting in a rapid decrease in the rate constants for ion production as n decreases (Zollars et al, 1986;Zheng, Smith, & Dunning, 1988;Carman, Klots, & Compton, 1989;Harth, Ruf, & Hotop, 1989). Using faster SF 6 molecules in a nozzle-jet expansion aids in the ion-ion separation and partially restores the ion signal at lower principal quantum numbers.…”
Section: Rydberg Electron Transfer (Ret) Tofmsmentioning
confidence: 95%